Analyzing Investor Reaction to PT Chandra Daya Investasi’s Initial Public Offering through Abnormal Returns and Trading Volume Patterns in the Prajogo Pangestu Group - Amanati, Nuzul; Sudaryo, Yoyo; Sofiati, Nunung Ayu; Ismail, Gurawan Dayona (SENTRALISASI, 2026)
This research investigates how the stock market responds to the Initial Public Offering of PT Chandra Daya Investasi Tbk (CDIA) and examines its influence on abnormal returns and trading volume activities of companies within the Prajogo Pangestu Group. The study applies an event-study approach to four affiliated issuers, namely BRPT, BREN, TPIA, and CUAN, using an 11-day event window around the IPO and a 60-day estimation period for return modeling. The analysis assesses whether CDIA’s listing generated meaningful price or trading-volume reactions within the group. The findings show that the IPO did not lead to significant abnormal returns or notable changes in trading activity for the affiliated stocks. Only a minor anticipatory response appeared on T–4, while neither the event day nor the days following it exhibited a meaningful market reaction. Overall, the results suggest that the CDIA IPO was treated as a firm-specific event with limited information spillover to other companies in the group.